Theoretical study of the effect of the element silicon, the adsorption enthalpy nitrite, on the surface of graphene nanostructure - Ahmadi, Roya; Farajpour, Eysa (Ciência e Natura, 2015)
The project is comparing four types of calculation derived graphene. To evaluate the effect of silicon element to Thermochemistry parameters of absorption of nitrite in these derivatives. Two of these derivatives of graphene carbon nitrite connection made, the difference is only in the state of Para and meta carbons connectivity state (named P & M). But in other Derivations first put silicon instead carbon in the meta and para position(named GER Si2 para & GER Si2 metha), then nitrite is added to the silicon(named P* & M*).